Bloom’s Taxonomy: Reforming Pedagogy Through Assessment (Journal of Education and Educational Development, 2021)
The study analyses the scope and role of Bloom’s Taxonomy in reforming teaching-learning practices in the classroom. Bloom’s Taxonomy propounds that teaching-learning process and assessment items should transcend beyond lower domains of learning i.e. remembering, understanding and applying to the higher domains of learning namely analysing, evaluating and creating. However, this study establishes that teacher always teach in accordance with the normative assessment patterns and students also learn accordingly. In this case, if assessment system is predominantly focused on lower domains, the teaching-learning practices will never transcend to higher domains. This study employs Bloom’s Taxonomy to categorise and analyse each item included in the annual question papers designed by the Boards of Intermediate and Secondary Education (BISE) Karachi, Hyderabad, Sukkur and Mirpurkhas for the subject of English for grade XII. At Sindh province level, it has been found that 74% is exhausted for the lower domains whereas only 26% is used for higher domains. Given to the normative assessment practices, teachers and students would remain focused only on the lower domains, but by altering the course, the pedagogical practices and teaching-learning process in Sindh province can remarkably be reformed and transformed from sheer memorization and rote-learning to critical thinking, solution-making, knowledge-building process and analytical skills